1988
DOI: 10.1002/jez.1402480207
|View full text |Cite
|
Sign up to set email alerts
|

Maternal triiodothyronine injections cause increases in swimbladder inflation and survival rates in larval striped bass, Morone saxatilis

Abstract: We have experimentally elevated the triiodothyronine ("3) content of striped bass (Morone saxutilis) eggs by injecting female striped bass intramuscularly with a large dose of T3 (20 pglg body weight) shortly before the induction of spawning. The significant elevation of T3 concentrations in the eggs from the hormone-injected fish (to 180 ng per gram), compared with those of vehicleinjected controls (about 19 nglg), confirms the transfer of T3 from the maternal circulation into oocytes. There were significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
1
2

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 20 publications
4
82
1
2
Order By: Relevance
“…As has been demonstrated for other fish species, it can be assumed that the halibut egg/yolk sack carries a maternal source of THs, as detectable levels of THs are found in the halibut larvae prior to 142 D°, when a few sporadic thyroid gland follicles first appear. The potential role of THs in early fish development is suggested from studies in which THs have been administered and shown to accelerate development and improve survival in round fish (Brown et al 1988;Brown and Kim 1995;de Jesus et al 1998). In addition, the inhibition of TH synthesis suggests that THs play an important role in fin and scale development in zebrafish larvae (Brown 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As has been demonstrated for other fish species, it can be assumed that the halibut egg/yolk sack carries a maternal source of THs, as detectable levels of THs are found in the halibut larvae prior to 142 D°, when a few sporadic thyroid gland follicles first appear. The potential role of THs in early fish development is suggested from studies in which THs have been administered and shown to accelerate development and improve survival in round fish (Brown et al 1988;Brown and Kim 1995;de Jesus et al 1998). In addition, the inhibition of TH synthesis suggests that THs play an important role in fin and scale development in zebrafish larvae (Brown 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the thyroid hormones (THs), thyroxine (T 4 ) and triiodothyronine (T 3 ), in vertebrate development is well established (Hadley 1992;Tata et al 1993;Power et al 2001). In fish, prior to the maturation of the larval thyroid gland, fish eggs and, subsequently, the larval yolk sack contain significant amounts of THs of maternal origin (Kobuke et al 1987;Tagawa and Hirano 1987;Brown et al 1988;Greenblatt et al 1989;Tagawa et al 1990a, b). This source of THs is likely to be of importance for the physiological regulation of growth, development and osmoregulation in larvae prior to the development of functional endogenous thyroid follicles.…”
Section: Introductionmentioning
confidence: 99%
“…In fishes, embryo and larval characteristics such as egg size, developmental rate, metabolism, growth and viability are affected by the body condition and genotype of the female parent (Chambers et al 1989, Chambers & Leggett 1996, Kerrigan 1997, Marteinsdottir & Steinarsson 1998. Non-genetic maternal contributions take many forms that directly influence survival probabilities of larvae, including nutritional reserves (Kerrigan 1997), levels of developmental and metabolic hormones (Brown et al 1988, McCormick 1998, 1999, and parental care (Bernado 1996). While paternal effects have been identified in fishes (Heath et al 1993, Herbinger et al 1995, Hoie et al 1999a, Yamamoto & Reinhardt 2003, they are not detectable in all larval traits (Hoie et al 1999b), and are often not considered.…”
Section: Introductionmentioning
confidence: 99%
“…A partir daí, as larvas controle atingiram valores mais elevados e significativamente diferentes (P<0,05), em função de que o canibalismo, na fase inicial da vida destes peixes, foi mais acentuado no controle resultando em baixa taxa de sobrevivência deste grupo (Figura 4). A administração de hormônios tireóideos em fêmea reprodutora de truta arco-iris mostrou aumento no crescimento, inflação mais rápida da bexiga natatória e maior sobrevivência da prole, sugerindo transferência materna (Brown et al, 1988;Ayson & Lan, 1993).…”
Section: Indução Hormonal Da Reproduçãounclassified
“…Sullivan et al (1989) mostraram que T3 aumentou significativamente o potencial do hormônio liberador de gonadotropina sintética análoga de mamífero (GnRHa), na indução da ovulação em truta arcoíris (Oncorhynchus mykiss), presumivelmente pela potencialização da GtH. Administração de hormônios tireóideos em fêmea reprodutora de truta-arco-íris mostrou aumento no crescimento, inflação mais rápida da bexiga natatória e maior sobrevivência da prole (Brown et al, 1988;Ayson & Lam, 1993).…”
Section: Introductionunclassified